Analisis dan Perancangan Sistem Informasi Penjualan pada Toko XYZ - Erlanie Sufarnap; Mirza Ilhami; Jefri Junifer Pangaribuan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
Along with the development of the times in the field of technology, companies are increasingly being triggered to use advanced technology as a tool or medium to survive and win the increasingly fierce competition. Internet technology has been proven to be one of the effective and efficient information media in disseminating information that can be accessed by anyone, anytime and anywhere. Internet technology has a huge effect on commerce or business. XYZ Store is a trading business engaged in the sale of plastic. The sales system at the XYZ store still uses a manual system and does not use more competent and computerized technology. The plastic sales transaction system that is done manually requires computerized data collection as a tool. Due to these problems, it is necessary to do research to find solutions that can solve problems at the XYZ store. The results of the research are the construction of a web-based plastic sales information system that makes it easier for users to place orders and payments through a computerized system that was built. Through this web information system, XYZ store can reach more customers from various provinces and cities in Indonesia.